ADAB MENUNTUT ILMU DI ERA KONTEMPORER MENURUT HADIS - Fikriyyah, Hurin; Cendani, Aliffia Hati; Firnanda, Cassano Vany (Al-Bayan: Journal of Hadith Studies, 2023)
This research aims to better understand, study, and deepen understanding of the etiquette and ethics of seeking knowledge according to the hadith. The method used in this research is a descriptive qualitative approach with historical and comparative approaches, while the analysis technique utilizes descriptive analysis techniques through a qualitative approach in the form of descriptions. The academic problem in this research concerns the procedures or attitudes that Muslims should adopt when seeking knowledge so that it benefits themselves and others, based on the hadiths of the Prophet Muhammad (peace be upon him). The successful research results demonstrate that seeking knowledge properly and correctly according to the teachings of Islam through the hadiths of the Prophet (peace be upon him), can guide Muslims to acquire beneficial and blessed knowledge. Morality is the most important quality a person must possess to achieve the blessing of knowledge. Through knowledge, humans can develop their potential, and knowledge is considered the starting point for developing the attitudes of every Muslim.